2021
DOI: 10.1080/21655979.2021.1979863
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Schisandrin B against D-GalN-induced cell apoptosis in human hepatocyte (L02) cells via modulating Bcl-2 and Bax

Abstract: Schisandrin B is a dibenzocyclooctadiene derivative extracted fromSchisandra chinensis (Turcz.) Baill., that exhibits anti-oxidation, anti-inflammation, anti-tumor and hepatoprotective activities. To understand the hepatoprotective mechanism of schisandrin B, this study investigated the efficacy of schisandrin B on L02 cells after treatment with D-GalN. Following pretreatment with 40 μM schisandrin B, L02 cells were stimulated with 40 mM D-GalN. Cell viability, apoptosis, the expression levels of genes associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“… 20 Studies have reported that Sch B can effectively prevent cell apoptosis, slow down fibrosis progression, induce cytochrome P450 (CYP) enzyme activity, and promote liver regeneration. 21 , 22 , 23 In addition, several studies have demonstrated that Sch B can inhibit the growth of various types of cancers, including lung cancer, cholangiocarcinoma, gastric cancer, melanoma, and glioma, by inducing cell-cycle arrest or apoptosis. 20 Sch B alleviates myocardial ischemia-reperfusion injury, 24 drug-induced hepatotoxicity 25 and nephrotoxicity 26 by reducing oxidative stress and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Studies have reported that Sch B can effectively prevent cell apoptosis, slow down fibrosis progression, induce cytochrome P450 (CYP) enzyme activity, and promote liver regeneration. 21 , 22 , 23 In addition, several studies have demonstrated that Sch B can inhibit the growth of various types of cancers, including lung cancer, cholangiocarcinoma, gastric cancer, melanoma, and glioma, by inducing cell-cycle arrest or apoptosis. 20 Sch B alleviates myocardial ischemia-reperfusion injury, 24 drug-induced hepatotoxicity 25 and nephrotoxicity 26 by reducing oxidative stress and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many miR-21 target genes are closely associated with carcinogenesis and tumor development [20,21]. For example, TPM1 participates in the formation of cytoskeleton structure [22]; PDCD4 inhibits cell growth [23]; phosphatase and tensin homolog (PTEN) inhibits cell migration and proliferation [24]; reversioninducing-cysteinerich protein with kazal motifs (RECK) inhibits tumor invasion and metastasis [25]; Bcl-2 inhibits cell apoptosis [26], and TIMP3 is involved in the induction of cell apoptosis by extracellular signals [27]. Interestingly, previous study also found that miR-21 level correlates with chemosensitivity in advanced pancreatic cancer [28], and miR-21 inhibitor could ameliorate Gem chemosensitivity [29].…”
Section: Introductionmentioning
confidence: 99%